2009
DOI: 10.1007/s10995-009-0481-2
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Pubertal Status with a Chinese Self-report Pubertal Development Scale

Abstract: This cross sectional study of 290 Chinese children aged 8-18 years, evaluated a Chinese version of the self-reported Pubertal Development Scale (PDS) against both raters' and self-reported Tanner assessment of pubertal status. Children completed both the self-reported PDS and self-reported Tanner pubertal questionnaire prior to physical examination through visual depiction by a same gender rater. Puberty Category Scores (PCS) which were derived from the PDS, was used to categorize children into one of five pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 29 publications
6
48
0
1
Order By: Relevance
“…Una posible limitación es la valoración de la maduración puberal mediante auto-reporte, técnica ampliamente utilizada en estudios poblacionales, siendo la concordancia entre el personal de salud y el auto-reporte adecuada en ambos sexos, aunque mejor en las niñas 42 . Estudios recientes en población china apoyan el uso del auto-reporte 43,44 , sin cuestionarse su uso en estudios poblacionales, mientras que para estudios clínicos o individuales se requiere complementar con evaluación especializada. Otra limitación es la falta de representación de edades < 10 años y de post-púberes.…”
Section: Discussionunclassified
“…Una posible limitación es la valoración de la maduración puberal mediante auto-reporte, técnica ampliamente utilizada en estudios poblacionales, siendo la concordancia entre el personal de salud y el auto-reporte adecuada en ambos sexos, aunque mejor en las niñas 42 . Estudios recientes en población china apoyan el uso del auto-reporte 43,44 , sin cuestionarse su uso en estudios poblacionales, mientras que para estudios clínicos o individuales se requiere complementar con evaluación especializada. Otra limitación es la falta de representación de edades < 10 años y de post-púberes.…”
Section: Discussionunclassified
“…Sexual maturity was assessed by self-report using the indices of pubic hair described by Tanner (1962). Pre-pubertal status was defined as Tanner stage 1 ( n  = 12), with stage 2 being early pubertal ( n  = 4), Tanner stage 3 mid-pubertal ( n  = 4), Tanner stages 4 and 5 being late pubertal, and post pubertal, respectively (Chan et al 2010). To provide an additional indicator of physical maturity, the age to peak height velocity equation devised by Mirwald et al (2002) was used based on the measurement of standing and seated height, weight, and age to calculate maturity offset.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies therefore rely on self-assessment questionnaires with pictures or questions or on the use of a pubertal development scale, where children are asked to rank their development. [9][10][11][12] Previous investigations of the reliability of self-assessment have shown conflicting results. Some studies found reasonable agreement between self-assessment and examination by a physician, [13][14][15][16] whereas others found discrepancies.…”
mentioning
confidence: 99%